2000
DOI: 10.1007/bf02236732
|View full text |Cite
|
Sign up to set email alerts
|

Operative mortality rates among surgeons

Abstract: The Portsmouth predictor equation for mortality equation seems to be a more accurate predictor of mortality in gastrointestinal surgery. It would seem to provide the best choice for analyzing operative mortality rates for individual surgeons, taking into account variation in case mix and fitness of patients even when scored retrospectively. This has important implications for the future assessment of surgeons' clinical standards and the assessment of quality of surgical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(14 citation statements)
references
References 14 publications
2
9
0
1
Order By: Relevance
“…The decision to withdraw treatment should be based on validated prognostic scales that are used to objectively assess the general condition based on physiological variables and factors associated with greater perioperative mortality. Most reports [13,16,17]. Our study showed that the scores of the P-POSSUM scale corresponded closely with the actual treatment outcomes of patients with acute mesenteric ischemia.…”
Section: Discussionsupporting
confidence: 75%
“…The decision to withdraw treatment should be based on validated prognostic scales that are used to objectively assess the general condition based on physiological variables and factors associated with greater perioperative mortality. Most reports [13,16,17]. Our study showed that the scores of the P-POSSUM scale corresponded closely with the actual treatment outcomes of patients with acute mesenteric ischemia.…”
Section: Discussionsupporting
confidence: 75%
“…The POSSUM score is calculated using a combination of 12 physiological and 6 operative data variables for each patient to calculate percentage risk. Originally developed in 1991 by Copeland et al (Copeland et al 1991 ), it has been evaluated widely, including in orthopaedic, vascular, head and neck and colorectal surgeries (Mohamed et al 2002 ; Prytherch et al 2001 ; Myers 1993 ; Griffiths et al 2002 ; Tekkis et al 2000 ). The OS-MRS uses a binary point scoring system based on five variables to stratify patients into three main groups (DeMaria et al 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…As expected, the 2 older cohorts of patients appeared to be at greater risk, as demonstrated by a higher percentage of patients with an American Society of Anesthesiologists' score of 3 or 4 and a higher predicted morbidity and mortality rate by POSSUM. [30][31][32][33][34]…”
Section: Commentmentioning
confidence: 99%